La densità come concetto chiave: un percorso verticale e fenomenologico - Caruso, Marco (Chimica nella Scuola, 2025)
This article presents a vertical teaching path on density, designed for students from middle school to university. A phenomenological approach and the macro-micro-symbolic triangle are used to build a progressive understanding of the concept. Common misconceptions and preconceptions are addressed, with experiments such as saline solution stratification supporting the correction of erroneous ideas. The article incorporates active teaching methodologies and reflects on how density can serve as a gateway to fundamental scientific literacy.